Maternal serum galectin-1 and galectin-3 levels in pregnancies complicated with preterm prelabor rupture of membranes - Kaya, Başak; Turhan, Uğur; Sezer, Salim; Kaya, Serdar; Dağ, İsmail; Tayyar, Ahmet (Taylor and Francis Ltd, 2020)
Objective: To investigate maternal serum galectin-1 and galectin-3 levels in pregnancies complicated with preterm prelabor rupture of membranes (PPROM) and to compare with pregnancies delivered at term. Materials and methods: In this cross-sectional study, 40 women with singleton pregnancies complicated with PPROM between 24 and 34 weeks of gestation were compared with gestational age-matched 40 pregnant women with no obstetrics complications, who delivered at term. The maternal serum galectin-1 and galectin-3 levels were measured. Results: Patients complicated with PPROM had significantly higher levels of galectin-1 (p = .001) and galectin-3 (p = .003) than the control group. Maternal serum galectin-3 levels were found significantly negatively correlated with the gestational age at delivery and birth weight. Conclusion: Maternal serum galectin-1 and galectin-3 levels were significantly higher in pregnancies complicated with PPROM. Galectin-1 and galectin-3, with their regulatory effects in key biological processes, may be both an initiating factor in the pathophysiology of PPROM, a marker in the prediction, and a target of preventing strategies of PPROM.
Keywords: Galectin-1; Galectin-3; Lectins; Preterm Birth; Preterm Prelabor Rupture of Membranes